2021
DOI: 10.1016/j.jaci.2021.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Sequestosome 1/p62 enhances chronic skin inflammation

Abstract: Background: The molecular control of inflammation and epidermal thickening in skin lesions of patients with atopic dermatitis (AD) is not known. Sequestosome 1/p62 is a multifunctional adapter protein implicated in the control of key regulators of cellular homeostasis, such as proinflammatory and mechanistic target of rapamycin signaling. Objective: We sought to determine whether p62 plays a role in the cutaneous and systemic manifestations of an AD-like mouse model. Methods: AD-like skin lesions were induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…Interestingly, these findings are reminiscent of our previously published data showing that AP-1 was also the major transcription factor for Ras-induced p62 mRNA expression in the tumor epithelium (Duran et al, 2008), which suggests that AP-1 is a hotspot for the upregulation of p62 by oncogenic transformation in the epithelium and its downregulation in the stroma. Regarding the composition of the AP-1 transcription factors mediating this effect in the stroma, our data identified c-FOS and c-JUN, but not FOSB or JUNB, in contrast with previous reports demonstrating that JUNB mediated repression of p62 in keratinocytes (Sukseree et al, 2021), which suggests that different AP-1 proteins may play distinct roles in p62 regulation under different cellular contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, these findings are reminiscent of our previously published data showing that AP-1 was also the major transcription factor for Ras-induced p62 mRNA expression in the tumor epithelium (Duran et al, 2008), which suggests that AP-1 is a hotspot for the upregulation of p62 by oncogenic transformation in the epithelium and its downregulation in the stroma. Regarding the composition of the AP-1 transcription factors mediating this effect in the stroma, our data identified c-FOS and c-JUN, but not FOSB or JUNB, in contrast with previous reports demonstrating that JUNB mediated repression of p62 in keratinocytes (Sukseree et al, 2021), which suggests that different AP-1 proteins may play distinct roles in p62 regulation under different cellular contexts.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, our study showed that LC3 levels and autophagic vesicles, the "gold standard" autophagy markers, were decreased in the epidermis of patients with AD as well as in different types of AD murine models compared with normal healthy subjects or normal mice. Moreover, p62, another frequently used autophagy-related marker, was increased in the AD epidermis, consistent with previous studies (6,14). The treatment of human keratinocytes with IL-4 and IL-13 has been used to mimic the features of AD in vitro (29).…”
Section: Discussionsupporting
confidence: 86%
“…Upregulation of microtubule-associated protein light chain 3-II (LC3-II) and downregulation of sequestosome-1/p62 (p62) result in autophagy activation (5). p62 acts as a selective autophagy adaptor and enhances inflammation in skin conditions, including AD and psoriasis, which are characterized by defects in the epidermal barrier and keratinocyte differentiation, through signaling of nuclear factor kappa-light-chain-enhancer of activated B cells and mechanistic target of rapamycin (mTOR) (6). mTOR functions as an upstream regulator of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory cytokines, such as IL-1β, TNF-α, and INF-γ, can enhance the process of autophagy through the activation of the mammalian target for rapamycin (mTOR) and AMP-activated protein kinase (AMPK) pathways [ 58 ]. Moreover, the important autophagy substrate, p62/SQSTM1, has been linked to the stimulation of chronic inflammation in the skin and myometrium through the activation of the NF-κB signaling pathway [ 59 , 60 ]. This molecule has been demonstrated as significantly elevated in the cellular models of cystinosis, particularly in PTECs [ 61 , 62 , 63 ].…”
Section: Interplay Between Inflammation Autophagy and Apoptosis In Cystinosismentioning
confidence: 99%